Acidificantes em dietas de leitões desmamados:desempenho , peso de orgãos, ph, morfometria e microbiota intestinal - Grecco, Henrique Augusto Travaini [UNESP] (2014)
Two experiments (E) were conducted to evaluate the effects of fumaric acid and an organic acid blend compound of calcium formate, calcium lactate and medium chain fatty acids (capric and caprylic) in piglets diets on performance and frequency of diarrhea (E 1), relative organ weight, pH, morphometry and intestinal microbiota (E 2). One hundred and ninety two (E 1) and twenty four (E 2) piglets weaned at 21 days, distributed in a randomized block design with a 2x2 factorial arrangement of treatments (absence x presence of fumaric acid and absence x presence of acidifying product), six replications of eight and one pig per pen were used, respectively, for E 1 and E 2. In E 1, lasting 41 days, the treatments were: Control – No acidifying + 40 ppm of colistin sulfate; AF – Presence of fumaric acid and absence of acidifying product; MA – Presence of acidifying product and absence of fumaric acid and AF+MA: presence of fumaric acid and acidifying product. In E 2, lasting 14 days, Pré-Starter I diet was used and assessed the same treatments of E 1. There were no treatment effects (P>.05) in performance, incidence of diarrhea, gastrointestinal pH and morphometry of the duodenum of piglets, however, the addition of organic acid blend reduced (P<.05) the relative weight of the large intestine and the addition of fumaric acid increased the relative weight of the pancreas and decreased (P<.05) the villus height of jejunum and number of total coliforms and Escherichia coli in the cecum. The inclusion of fumaric acid and the organic acid blend in the diets of weaned piglets containing antibiotic is not justified, however, fumaric acid exerts an inhibitory effect on the population of coliforms and Escherichia coli